Fatigue prediction of composite materials, based on serial/parallel mixing theory. (1st July 2022) - Granados, Joel Jurado; Martinez, Xavier; Barbu, Lucia G.; Di Capua, Daniel
Abstract: In this work, a numerical procedure to obtain the fatigue performance of composite laminates is proposed. The formulation used is based on the Serial/Parallel Mixing Theory (SP-RoM) and a fatigue damage model. The SP-RoM acts as a constitutive law manager, obtaining the mechanical performance of the composite by solving the behaviour of each constituent material. The fatigue damage model modifies the constitutive performance of the composite constituents in order to consider the degradation of their mechanical properties due to cyclic loading. The proposed formulation is validated for two composite systems, a carbon/epoxy system and a glass/ polyester system. In addition, different composite configurations are numerically evaluated and compared with experimental data, in order to prove the capabilities of the formulation. All results prove that the numerical procedure develop is an excellent tool for obtaining the fatigue life and failure mechanisms of composite materials.